Exploring undergraduate students’ experiences in dealing with post-editing of machine translation - Harto, Sri; Hamied, Fuad Abdul; Musthafa, Bachrudin; Setyarini, Sri (Indonesian Journal of Applied Linguistics, 2022)
Although post-editing of machine translation (PEMT) has been much discussed and spoken among students in higher education institutions, little empirical evidence has been reported regarding the students’ real practices in their academic life. To fill this practical gap, this article explores the students’ experiences in dealing with PEMT in a Theoretical Foundation of Translating and Interpreting (TFTI) course. This exploration elaborates practical insights into how the students initially started practicing translation through PEMT in their actual day-to-day practices. Fifty-eight English students studying in an undergraduate program in a prominent public university in Indonesia voluntarily participated in this qualitative case study. Data were collected from students’ focused-group discussion (FGD), survey questionnaire, in-depth interviews, and students’ documents and the data were analyzed using thematic analysis. Findings showed that post-editing process provides the students with experiences in building their text knowledge to enable them to have high awareness and sensitivity to the academic texts. In addition, in PEMT practices, the students’ experiences were explored through the implementation of translation methods and techniques expected to build their awareness in PEMT with regard to language structure and language function. These experiences have given some empirical inputs for the lecturers to design relevant tasks and apply various translating practices for students’ more meaningful learning.